Life and loyalty : a study in the socio-religious culture of Syria and Mesopotamia in the Graeco-Roman period based on epigraphical evidence - Dijkstra, Klaas. (Religions in the Graeco-Roman World, 1995)
The formula 'for the life of' is often found in votive inscriptions, cast in Aramaic and other languages, which originate from the Syrian-Mesopotamian desert and adjacent areas and which roughly date from the first three centuries A.D. They belong to objects like statues and altars that usually were erected in temples and other structures with a ritual or sacred function. The inscriptions establish a relationship between the dedicator and one or more beneficiaries, those persons for whose life the dedication was made. Since the social context evidently bears on both the meaning of the inscriptions as well as the status of the dedications, this volume deals with the nature of the relationships and the socio-religious function the dedications perform.